Comparative Analysis Of Profit Management Of Plantation Companies Listed On The Indonesia Stock Exchange And The Malaysia Stock Exchange In The 2016-2018 Period - Mukhzarudfa, Mukhzarudfa; Jumaili, Salman; Izzuddin, Muhammad (Jurnal Cakrawala Akuntansi, 2024)
This study aims to analyze earnings management practices in plantation companies listed on the Indonesia Stock Exchange during the 2016–2018 period using the discretionary accrual approach. The study employs secondary data derived from published financial statements, including asset data, net income, and cash flows. The analysis methods consist of both descriptive and inferential statistical techniques. Discretionary accruals were used as a proxy to detect earnings management behavior.The results reveal that both Indonesian and Malaysian plantation companies engaged in earnings management practices, as indicated by the presence of both positive and negative discretionary accrual values. Descriptive analysis shows that the average discretionary accruals of Indonesian plantation companies are higher than those of Malaysian plantation companies over the observed period. However, inferential analysis using the Independent Sample T-Test indicates that there is no statistically significant difference in the extent of earnings management between plantation companies listed on the Indonesia Stock Exchange and those listed on Bursa Malaysia. Moreover, the average discretionary accruals reflect a negative value, suggesting that earnings management was predominantly conducted through income-decreasing strategies.This study contributes to the comparative financial reporting literature by providing empirical evidence on earnings management behavior in the Southeast Asian plantation sector. The findings offer insights for regulators, auditors, and investors regarding the quality of reported earnings and the financial transparency of publicly listed agricultural firms.